2003
DOI: 10.1097/00000372-200308000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Proliferation- and Apoptosis-Related Markers in Lentigo Maligna and Solar Keratosis Keratinocytes

Abstract: Keratinocytes influence the number, morphology, and proliferation of melanocytes. An interference in the melanocyte-keratinocyte relationship may contribute to melanoma development. This study examined the expression of apoptotic and proliferative markers in keratinocytes in lentigo maligna to characterize the epidermis permissive to these lesions. Formalin-fixed and paraffin-embedded tissues from 25 samples of lentigo maligna, 20 samples of solar keratoses, and 5 samples each of normal sun-exposed and non-sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 37 publications
6
23
0
2
Order By: Relevance
“…and one performed by Feinmesser et al 46 . Feinmesser analysed Bcl‐2 expression in 20 AK and revealed positivity in only 35% of cases 46 . In our study, all investigated AK showed Bcl‐2 expression but the majority was weakly positive, and only 41.7% of investigated AK had stronger immunoreaction than unaffected perilesional skin that is consistent with results in the literature 36,37,46 .…”
Section: Discussionsupporting
confidence: 92%
“…and one performed by Feinmesser et al 46 . Feinmesser analysed Bcl‐2 expression in 20 AK and revealed positivity in only 35% of cases 46 . In our study, all investigated AK showed Bcl‐2 expression but the majority was weakly positive, and only 41.7% of investigated AK had stronger immunoreaction than unaffected perilesional skin that is consistent with results in the literature 36,37,46 .…”
Section: Discussionsupporting
confidence: 92%
“…20 Mutations in the keratinocyte p53 molecule, because of the effects of chronic UV exposure, causes a cascade of events leading to an epidermis that is fertile ground for mutated junctional melanocytes that could evolve into malignant melanoma in situ. 19 Although we view the presence of an associated solar lentigo to be primarily a diagnostic pitfall in the diagnosis of LM, the possibility that they could represent a precursor lesion deserves further study. Pigmented lesions suspicious for LM are typically mottled rather than homogeneous.…”
Section: Discussionmentioning
confidence: 86%
“…[17][18][19] Interference in keratinocyte and melanocyte contact and communication via the adhesion molecule Mel-CAM has been found to contribute to melanoma development. 20 Mutations in the keratinocyte p53 molecule, because of the effects of chronic UV exposure, causes a cascade of events leading to an epidermis that is fertile ground for mutated junctional melanocytes that could evolve into malignant melanoma in situ.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that UV radiation induces the formation of sunburn cells, which are apoptotic cells with increased expression of proapoptotic proteins, such as p53 and bax, and decreased expression of anti‐apoptotic proteins such as bcl‐2. Ki‐67 expression is also increased in sunburn cells (22–27).…”
Section: Introductionmentioning
confidence: 99%